A child with mastocytosis and lymphomatoid papulosis - Lange, Henriette Juel (Clin Case Rep, 2016)
A change in clinical behavior of a disease should prompt search for differential diagnoses. Here, the appearance of ulcerated skin nodules in a preexisting cutaneous mastocytosis revealed a concurrent lymphomatoid papulosis – a CD30+ lymphoproliferative skin disease with histological features of a malignant lymphoma, but with a benign self‐healing course.